Robustness analysis of deteriorating reinforced concrete slabs - Cavaco, Eduardo S. (2012)
Corrosion of reinforcement bars in concrete structures is the most significant deterioration mechanism in these structures. Corrosion is extremely difficult to predict and, consequently, can be regarded as an unpredictable event. Following this, robustness assessment methods can be employed to define the susceptibility of a structure to corrosion. In this work, robustness is measured in terms of the remaining safety of a deteriorated structure. The proposed methodology is illustrated by means of a reinforced concrete (RC) slab subjected to dead and live loads. The performance of the corroded slab is evaluated using non-linear analysis. The reliability index is adopted to assess the safety of the deteriorated structure. To compute the reliability index a strategy combining the First Order Reliability Method (FORM) and the Response Surface Method (RSM) is used.